Pulmonary tomographic changes in COVID-19: integrative literature review (Research, Society and Development, 2021)
Aim: The general objective of this study was to analyze scientific publications on findings from images related to COVID-19 in multidetector computed tomography scans. Methodology: This is an integrative literature review searching on databases of the Bliblioteca Virtual da Saúde, PubMed and Google Scholar, using as descriptors “Coronavirus Infections”, “Pneumonia” and “Multidetector Computed Tomography”. The following inclusion criteria were used: those that addressed the theme COVID and CT; articles available in Portuguese, English or Spanish. Gray literature material was excluded. Results and discussion: nine articles matched with the selected criteria, being separated into three main variables, namely: typical and atypical radiological findings; evolution of tomographic findings and severity and; incidental diagnosis of COVID-19 on CT. Tomographic findings showed the presence of ground-glass opacity, paving, mosaic consolidation, reticular pattern, the inverted halo sign and, in children, pleural thickening and patterns such as bronchial pneumonia and asthmatic bronchitis. CT makes it possible to describe the evolution of COVID-19, as each finding is fundamentally predominant in a certain phase of disease progression. It may also be used as an assessment and definition of the severity of the condition. Conclusion: In spite of multidetector CT is not the first choice for assessment patients with COVID-19, it provides information about the disease with a high degree of sensitivity, allowing the identification of typical and atypical findings that can be decisive in the diagnostic process, in addition to be a strategy for monitoring the evolution and severity of cases of COVID-19.